(3eHGOF GdGbJUGO GdLRFj (B/s - (3GdfUQ, eMeO eMehOs; (3TGejI, YHO Gddg eMeO s ((3YeGf(B: s (3OGQ GdCed(B, s, 1989)
(3eaGgje YGeI,eG gh GdGbJUGO,GdWdH hGdYQV,GdeQhfI,Sdhc GdeSJgdc,GdGfJGL hGdJcGdja,GdefGaSI GdcGedI,GdGMJcGQ GdJGe,GdefGaSI GdGMJcGQjI,GMJcGQ GdbdI,Shb YfGUQ GdGfJGL,ehGVjY NGUIs
(3GdeUWdMGJ HGdCfLdjRjI U(B.374s
Keywords: (3GdGbJUGO GdLRFjs